2017
DOI: 10.1111/cen.13315
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of known interventions for the treatment of chronic nonhypovolaemic hypotonic hyponatraemia and a meta‐analysis of the vaptans

Abstract: International and national guidelines on the treatment of chronic nonhypovolaemic hypotonic hyponatraemia differ; therefore, we have undertaken this systematic review and metaanalysis to investigate the efficacy and safety of interventions for the treatment of chronic nonhypovolaemic hypotonic hyponatraemia. Following registration of the review protocol with PROSPERO, systematic literature searches were conducted to identify randomized and quasi-randomized controlled trials assessing any degree of fluid restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
(171 reference statements)
2
20
1
7
Order By: Relevance
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of brain damage, Bhandari et al 31 effectively attenuated the brain edema secondary to intracerebral hemorrhage (ICH) in animals treated with Tolvaptan, an AVP-V2 receptor antagonist; they also showed a decrease in BBB permeability to Evans blue tracer in the Tolvaptan-treated ICH animals as compared to the ICH group 31 . Other animal experiments found that blockade of AVP-V1 receptors reduces brain edema and BBB disruption in stroke 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of brain damage, Bhandari et al 31 effectively attenuated the brain edema secondary to intracerebral hemorrhage (ICH) in animals treated with Tolvaptan, an AVP-V2 receptor antagonist; they also showed a decrease in BBB permeability to Evans blue tracer in the Tolvaptan-treated ICH animals as compared to the ICH group 31 . Other animal experiments found that blockade of AVP-V1 receptors reduces brain edema and BBB disruption in stroke 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the author is truly convinced that it is worth to correct hyponatremia in patients, including cancer patients, because of the overall beneficial effect on the quality of life, which includes clinical improvement, such as amelioration of neurocognitive and motor performance, reduced length of stay in the hospital and re-admission probability [44][45][46] .…”
Section: Resultsmentioning
confidence: 99%
“…These drugs increase renal excretion of solute‐free water and have been used for the treatment of nonhypovolemic hyponatremia when routine therapy is ineffective or when long‐term treatment is necessary. A recent meta‐analysis reported that vaptans significantly improve serum [Na + ] when compared to placebo, although they have been associated with an increased likelihood of overly rapid correction of serum [Na + ], and adverse effects including liver injury have been reported . The vaptans are not currently recommended for routine therapy of hyponatremia in human medicine and their exact role remains controversial …”
Section: Diagnosismentioning
confidence: 99%